Influence of Gender, Management and Locality of Schools on the Thinking Styles of Secondary School Students in Kerala - Ramakrishnan, P.; Naseema, C. (INDIAN EDUCATIONAL REVIEW, 2013)
The influence of gender, management category of schools and locality of schools on the thinking styles as defined by the mental self government theory of Sternberg (1997) was studied. A Thinking Styles Test Battery (TSTB) was developed and administered among 486 secondary school students (228 boys and 258 girls) studying in 9th standard randomly selected from 13 schools among six districts in Kerala State. It was found that gender is influencing internal, liberal and conservative thinking styles. Boys are found to be highly internal and liberal than girls and girls are high in their conservative thinking style characteristics. It was also revealed that management category of the student’s schools is also influencing some thinking styles. Students studying in aided schools are significantly high in their monarchic, hierarchic and internal thinking styles whereas students studying in government schools are high in their executive thinking styles. Locality of the schools is also found to be influencing the thinking styles of students. Urban pupils have significantly high legislative thinking style and rural pupil have significantly high judicial and monarchic thinking styles.